A contribuição da defensoria pública na promoção do acesso à justiça por minorias e grupos vulneráveis - Freire, Jéssika de Lima (2022)
In Brazil, disrespect for the fundamental rights of minorities and groups vulnerable is clear. Indeed, the dignity of the human person requires that specific protection is granted to these subjects as a way of mitigating the effects of their peculiar condition of vulnerability. However, situations of negligence, cruelty and oppression persist openly, among which are highlight the difficulties in accessing justice. Access to justice, understood in its broad meaning, which is not limited to mere access to the Judiciary, is the means by which those individuals can claim their rights, correcting the From this, situations of disrespect. The Public Defender's Office assumes a role essential in achieving this task, as it is responsible for promoting full and free legal assistance to such subjects, whose actions, however, is permeated with challenges that can compromise the effectiveness of the relevant constitutional command. Given this context, the present research aimed to demonstrate that the difficulties faced by minorities and groups vulnerable in access to justice further compromise the exercise of their rights. To this end, bibliographical research was carried out on national and foreign language related to the topic, as well as documentary research in Brazilian legislation. The results obtained confirm the initial thesis that There is still a lot to be done to strengthen the Public Defender's Office as a institution of the justice system and, consequently, strengthen the rights of people who make up your target audience. It was also found that the social transformation is linked to the promotion of the rights of the of the population that is marginalized, whose implementation must be the incessant search for a society that proclaims itself democratic.